2018
DOI: 10.1155/2018/1687097
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Expression of miR-362 Promotes Lung Cancer Metastasis through Downregulation of Sema3A

Abstract: miR-362 is a recently discovered member of the microRNA family, and it modulates a variety of physical activities and plays an important role in the occurrence and development of many tumors. However, the biological functions of hsa-miR-362-5p in non-small-cell lung carcinoma (NSCLC) are unknown. Transwell assay and colony formation were used to determine the migration, invasion, and proliferation of NSCLC cells in vitro. A subcutaneous tumor model in nude mice was established to detect NSCLC tumor growth in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 38 publications
2
24
0
Order By: Relevance
“…Some reports suggest that Sema3A acts as a tumor suppressor in certain cancers [30,31]. In contrast, other researchers have shown that Sema3A alters tumor cell behavior directly by influencing migration and growth, or indirectly by interfering with tumor angiogenesis and the immune response [1,24,32,33]. Our findings agree with the results derived from other solid tumors, including pancreatic, lung, and prostate cancers [20,21,23].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Some reports suggest that Sema3A acts as a tumor suppressor in certain cancers [30,31]. In contrast, other researchers have shown that Sema3A alters tumor cell behavior directly by influencing migration and growth, or indirectly by interfering with tumor angiogenesis and the immune response [1,24,32,33]. Our findings agree with the results derived from other solid tumors, including pancreatic, lung, and prostate cancers [20,21,23].…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, Sema3A can affect cell phenotype indirectly by interfering with tumor angiogenesis and the immune response [12,13]. On the other hand, several reports suggest that Sema3A may be a potent tumor suppressor in oral and lung cancers [23,24]. Whether Sema3A functions as a tumor suppressor or tumor promoter is still unclear and may be cancer specific.…”
Section: Introductionmentioning
confidence: 99%
“…Studies found that miR-362-5p reduces the expression of tumor suppressor protein CYLD, which leads to activate the NF-kB pathway to promote the proliferation, migration, and invasion of hepatocellular carcinoma cells and human breast cancer cells (Ni et al, 2015;Ni et al, 2016). In addition, miR-362-5p directly binds and negatively regulates the expression of Semaphorin 3A (Sema3A) in non-small cell lung cancer (NSCLC) to enhance the cell invasion and migration in vitro and tumor formation in vivo (Luo et al, 2018). However, miR-362-5p also exhibits a tumor suppressive role in neuroblastoma by inhibiting cell proliferation and migration through PI3K-C2b (Wu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The biological functions of miR-362-5p have been extensively reported in various types of cancers. Increasing numbers of studies indicate that miR-362-5p promotes cell proliferation, tumor growth, and metastasis in hepatocellular carcinoma, human breast cancer, and lung cancer (Ni et al, 2015;Ni et al, 2016;Luo et al, 2018). However, miR-362-5p inhibits proliferation and migration of neuroblastoma cells and it is downregulated in renal cell carcinoma (Wu et al, 2015;Ying et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Also, the negative correlation between miR-362 expression and Sema3A expression was observed in clinical NSCLC tissue samples. Aberration of the miR-362/Sema3A axis might be the molecular mechanism of NSCLC invasion and migration and could lead to a potential therapeutic target in NSCLC treatment [36]. Semaphorins are a large family including at least 30 members which are divided into 3 types: secretory, transmembrane, and GPI-anchored, and 8 subgroups.…”
Section: Discussionmentioning
confidence: 99%